Efficacy of colonoscopy after an episode of acute diverticulitis and risk of colorectal cancer - Díaz, Jeancarlos Jhosmer Trujillo (Ann Gastroenterol, 2020)
BACKGROUND: Diverticular disease of the colon has a high global prevalence. The guidelines suggest performing a colonoscopy 4-6 weeks after the acute episode to exclude colorectal cancer (CRC). However, these recommendations are based on old studies, when computed tomography was not used to diagnose acute diverticulitis (AD). There are currently some studies showing that CRC incidence is low in uncomplicated AD (UAD). Therefore, we decided to perform this study to determine the CRC incidence after an AD episode and the diagnostic efficacy of colonoscopy in these patients. METHOD: This was a retrospective cohort study that included patients with AD between July 2016 and December 2017. RESULTS: One hundred seventy-four patients had AD. Of these, 46 patients were excluded and we analyzed 128 patients, 72 (56.3%) women and 56 (43.7%) men. Ninety (70.3%) had UAD and 38 (29.7%) complicated AD (CAD). The colonoscopy showed lesions in 18 (14.06%), 5 (3.9%) being CRC. The patients with CRC had shown CAD and were >70 years old (P=0.0001 and P=0.002 respectively). CONCLUSIONS: Routine colonoscopy in patients with UAD appears not have many benefits as a diagnostic tool. However, it has a higher efficacy if the patients have CAD and are >70 years old.